Retrospective analysis of spectrum of soft tissue tumors in a tertiary care center in Pakistan - Sikandar, Bushra (International Journal of Pathology, 2024)
Background: It is of uttermost importance to compile soft tissue tumor spectrum in the current study population which would not only aid in patient’s diagnosis but also open query for new molecular targets. Hence, this article aimed to study the frequency of different types of soft tissue tumors in a tertiary care hospital and to assess the correlation of the tumor with clinical parameter including gender, age, laterality, and site of soft tissue tumors. In addition, to generate national level statistics and estimate burden of disease. Methods: A retrospective study was carried out at Dow Diagnostic Research and Reference Laboratory (DDRRL) in Karachi, Pakistan from 2013 to 2019. All specimens related to soft tissue tumors received in DDRRL were recruited by PACS link software and through departmental records. Further, with the help of a clinical history, radiological work, morphology and IHC staining, diagnosis was made. Results: A total of 374 soft tissue tumor cases with 16 different types of tumors were identified. Of which Fibrous histiocytoma and rhabdomyosarcoma represented majority of cases (12.8% each). A total of 22 tumor sites were recognized, of which most types of tumors were found in bone mass (13.1%) and 27.3% cases represented left laterality. When the tumor type was assessed in association with clinical parameters, significant results were achieved for age (P-value = 0.000) and tumor site only (P-value = 0.000). Conclusion: This article provided the frequency of some major soft tissue tumor types found in Karachi, Pakistan. This study would not only aid in presenting the estimation of soft tissue tumor burden but would also provide awareness to the general population to seek help at early stage.